2022
DOI: 10.1108/jcrpp-03-2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

Digital displacement of youth offending: scoping and understanding the issue

Abstract: Purpose Global evidence suggests that youth offending has reduced; however, this study aims to suggest a more complex picture, with youth crime potentially being displaced to the digital space. Historically, young people and crime have been synonymous with public spaces and being visible. A shift or expansion to online offending requires revision of how the justice and educational systems respond to youth offending. Design/methodology/approach A systematic literature review explored keywords related to age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…An extensive systematic literature review explored global trends in the digital displacement of youth offending, within which academic and grey literature sources between 2012 and 2022 were reviewed, finding evidence to support the digital displacement of youth offending (McCord et al , 2022). Within this review, pathways from acceptable to deviant or criminal behaviour were also identified as relevant to the general issues of digital youth offending.…”
Section: Current Review and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive systematic literature review explored global trends in the digital displacement of youth offending, within which academic and grey literature sources between 2012 and 2022 were reviewed, finding evidence to support the digital displacement of youth offending (McCord et al , 2022). Within this review, pathways from acceptable to deviant or criminal behaviour were also identified as relevant to the general issues of digital youth offending.…”
Section: Current Review and Synthesismentioning
confidence: 99%
“…The literature supports three areas of digital offending or harm, including digitally assisted crime, digitally dependent crime and digital harms, which approach but do not cross into illegal behaviour (McCord et al, 2022;Rokven et al, 2018;Weulen Kranenbarg et al, 2021). Digitally assisted crime refers to traditional criminal activities carried out either with the assistance of or migration to the online space.…”
Section: Introductionmentioning
confidence: 99%